A atuação bibliotecária e o uso das mídias sociais: uma análise das habilidades, desafios e perspectivas - Fernandes, Júlio César Pinto (2023)
It presents a study whose general objective is to analyze the librarian's role in relation to the use of social media in Brazilian university libraries, based on the analysis of infocommunication skills, the challenges and perspectives that involve them. Regarding the specific objectives, we sought to investigate how often librarians use social media in libraries; Analyze which skills librarians deem necessary for the use of social media; Understand the main challenges that librarians envision when using social media as a communication and dissemination tool for informational products and services and Identify new perspectives for librarians' work with the use of social media. The research is exploratory, qualitative and quantitative. Study participants are librarians who work in Brazilian university libraries, public and private, from the five regions of Brazil. A total of 75 librarians participated. Data collection was carried out through a semi-structured questionnaire prepared in Google Forms sent to librarians via email from the communication channel of the Brazilian Commission of University Libraries of the Brazilian Federation of Associations of Librarians, Information Scientists and Institutions. The results showed, regarding the use of media by librarians, most use such tools in their practices, although few have policies and guidelines for such use, which leads to problems related to the monitoring of publications on platforms and interaction with users. It was also evident that librarians are aware of which infocommunication skills are necessary for a critical and efficient performance in social media, but they face challenges that involve training for the acquisition of such skills, where a reflection is launched for the initial training of librarians. It concludes by pointing to a future, where librarians recognize the consolidation of the use of social media in their practices, which was enhanced in the context of the SARS-Cov2 pandemic, seeking, therefore, a re-signification of their practices and reflections on a new profile to be trained in undergraduate courses to train professionals with infocommunication skills.